Leveraging chromatin state transitions for the identification of regulatory networks orchestrating heart regeneration - Cordero, Julio; Elsherbiny, Adel; Wang, Yinuo; Jürgensen, Lonny; Constanty, Florian; Günther, Stefan; Börries, Melanie; Heineke, Jörg; Beisaw, Arica; Leuschner, Florian; Hassel, David; Dobreva, Gergana (Nucleic acids research, 2024)
The limited regenerative capacity of the human heart contributes to high morbidity and mortality worldwide. In contrast, zebrafish exhibit robust regenerative capacity, providing a powerful model for studying how to overcome intrinsic epigenetic barriers maintaining cardiac homeostasis and initiate regeneration. Here, we present a comprehensive analysis of the histone modifications H3K4me1, H3K4me3, H3K27me3 and H3K27ac during various stages of zebrafish heart regeneration. We found a vast gain of repressive chromatin marks one day after myocardial injury, followed by the acquisition of active chromatin characteristics on day four and a transition to a repressive state on day 14, and identified distinct transcription factor ensembles associated with these events. The rapid transcriptional response involves the engagement of super-enhancers at genes implicated in extracellular matrix reorganization and TOR signaling, while H3K4me3 breadth highly correlates with transcriptional activity and dynamic changes at genes involved in proteolysis, cell cycle activity, and cell differentiation. Using loss- and gain-of-function approaches, we identified transcription factors in cardiomyocytes and endothelial cells influencing cardiomyocyte dedifferentiation or proliferation. Finally, we detected significant evolutionary conservation between regulatory regions that drive zebrafish and neonatal mouse heart regeneration, suggesting that reactivating transcriptional and epigenetic networks converging on these regulatory elements might unlock the regenerative potential of adult human hearts.